EKSISTENSI DAN PERAN KOMISI YUDISIAL : PENGKAJIAN KONTEKS FILOSOFI, SEJARAH DAN TUJUAN PEMBENTUKANNYA DALAM DINAMIKA KETATANEGARAAN INDONESIA - Indra Permana, Tri Cahya (Jurnal Hukum dan Peradilan, 2014)
The urge formation of the external monitoring agency behavior of judges is very strong, in addition to the internal watchdog also doubts the collapsed state of the world has been made a member of the Assembly judiciary instituted Judicial Commission in Chapter IX of the 1945 Constitution in order to position stronger. Institutionalization KY in 1945 by members of the Assembly is not right. As the external monitoring agencies in other branches of power, the more precise KY institutionalization in law. Since instituted in Chapter IX of the 1945 Constitution with a two (2) authority, KY has experienced tidal peak KY authority which has 9 (nine) authority. Currently, KY authority remaining six (6) in which three (3) authority is independent, while three (3) other authorities are jointly Supreme Court. Additional authority granted to them proven KY contrary to the 1945 Constitution. Keywords: Existence, Roles, Judicial Commission